2009
DOI: 10.1007/s00467-008-1062-0
|View full text |Cite
|
Sign up to set email alerts
|

Randomized cross-over trial comparing albumin and frusemide infusions in nephrotic syndrome

Abstract: The contribution of hypoalbuminemia to impaired diuretic responsiveness can be overcome by administering larger doses of loop diuretics. However, the clinical efficacy of the combination of loop-acting diuretics with human albumin remains controversial. In the study reported here, 16 children with nephrotic syndrome and refractory edema were randomized in a cross-over trial to receive either the combination of 20% human albumin and frusemide infusion (HA+FU infusion group) or frusemide infusion alone (FU infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 24 publications
2
23
0
1
Order By: Relevance
“…Combination therapy of human albumin with diuretic agents can enhance the elimination of sodium and fluids. In previous studies, the combination of furosemide with human albumin was associated with a two-fold increase in urine volume, compared with furosemide monotherapy [28][29][30]. Understanding the side effects of the therapy is also required.…”
Section: Medical Therapy For Edemamentioning
confidence: 95%
“…Combination therapy of human albumin with diuretic agents can enhance the elimination of sodium and fluids. In previous studies, the combination of furosemide with human albumin was associated with a two-fold increase in urine volume, compared with furosemide monotherapy [28][29][30]. Understanding the side effects of the therapy is also required.…”
Section: Medical Therapy For Edemamentioning
confidence: 95%
“…As loop diuretics are 91-99% bound to serum albumin avoiding the glomerular filtration in the nephron, hypoalbuminemia decreases the amount of loop diuretics to be delivered to the site of action in the thick ascending limb of Henle's loop [6]. Some reports showed that patients with hypoalbuminemia (serum albumin level of around <2.5-3.0 g/dL) do not sufficiently respond to loop diuretics such as furosemide [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested in the literature that institutionalization and dissemination of guidelines or protocols in itself does not necessarily translate into changes in practices or into lasting clinical results. 21 Data from one study have shown that it takes five to ten years to achieve significant results from changes in practice after implementation of these instruments. 36 The process of establishing therapeutic guidelines should also be followed by continuing education, review of processes and monitoring of practices.…”
Section: Discussionmentioning
confidence: 99%